2011
DOI: 10.1016/j.kjms.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione‐S‐transferase enhances proliferation‐migration and protects against shikonin‐induced cell death in breast cancer cells

Abstract: Glutathione-S-transferase (GST) is a cytoplasmic protein responsible for detoxification, but the effect of the enzyme on cell biological events, including proliferation and migration, has never been reported. Thus, we evaluated the detoxification effect of in vitro-applied GST on cancer cell proliferation and migration. Assays for proliferation and migration of human breast cancer cells in the presence of GST were carried out. Binding of GST on the surface of the cancer cells was studied by flow cytometry. Det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…Migration assays were carried out according to our recent report [25] for the different concentrations of sjGST in BD Falcon 24-well culture plate (BD Biosciences). The cells were seeded in the plate wells with or without 1 mm tape stuck in the middle and grown to 100% confluent.…”
Section: Wound-healing Assays and Cell Countingmentioning
confidence: 99%
“…Migration assays were carried out according to our recent report [25] for the different concentrations of sjGST in BD Falcon 24-well culture plate (BD Biosciences). The cells were seeded in the plate wells with or without 1 mm tape stuck in the middle and grown to 100% confluent.…”
Section: Wound-healing Assays and Cell Countingmentioning
confidence: 99%
“…Glutathione-S-transferase (GST) is a cytoplasmic protein responsible for detoxification. The study by He et al (18) showed that cell proliferation and migration could be enhanced in greater concentrations of GST, where GST directly bound to the surface of the cancer cells. Glutathione-S-transferase activities were higher in the breast tumor than in the normal cytosolic fractions.…”
Section: Discussionmentioning
confidence: 99%
“…The A549 human lung adenocarcinoma cells obtained from the American Type culture collection (ATCC CCL‐185, Manassas, VI, USA) were maintained in L‐15 media containing 10% fetal bovine serum, 50 g/L penicillin, and 100 mg/L streptomycin (Hyclone Laboratories, Inc., Logan, UT, USA) at 37°C in a humidified chamber with replacement of the media every 2 days as described [43,44] with modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The entire process was carried out according to the protocol as reported [14,43], with some modifications in a predetermined period of 8 days where approximately 1000 cells were incubated in the 96‐well plates with L‐15 media, containing 10% fetal bovine serum at 37°C in an incubation chamber, with respect to HGF variant proteins ( NK1 , NK2 , NK3 , and NK4 ), GST at 4 nM. At each interval of 2 days, fresh media and proteins were added and plates were collected at the end of 2 days, 4 days, 6 days, and 8 days.…”
Section: Methodsmentioning
confidence: 99%